Indoleamine 2,3-Dioxygenase Activity During Acute Toxoplasmosis and the Suppressed T Cell Proliferation in Mice - Ufermann, Christoph-Martin; Domröse, Andreas; Babel, Timo; Tersteegen, Anne; Cengiz, Sevgi Can; Eller, Silvia Kathrin; Spekker-Bosker, Katrin; Sorg, Ursula Regina; Förster, Irmgard; Däubener, Walter (Frontiers in Cellular and Infection Microbiology, 2019)
Toxoplasma gondii (T. gondii) is an obligate intracellular parasite and belongs to the phylum Apicomplexa. T. gondii is of medical and veterinary importance, because T. gondii causes the parasitic disease toxoplasmosis. In human cells, the interferon-gamma inducible indoleamine 2,3-dioxygenase 1 (IDO1) is an antimicrobial effector mechanism that degrades tryptophan to kynurenine and thus limits pathogen proliferation in vitro. Furthermore, IDO is described to have immunosuppressive properties, e.g., regulatory T cell differentiation and T cell suppression in humans and mice. However, there is only little known about the role of IDO1 in mice during acute toxoplasmosis. To shed further light on the role of mIDO1 in vivo, we have used a specifically adjusted experimental model. Therein, we infected mIDO1-deficient (IDO−/−) C57BL/6 mice and appropriate wild-type (WT) control mice with a high dose of T. gondii ME49 tachyozoites (type II strain) via the intraperitoneal route and compared the phenotype of IDO−/− and WT mice during acute toxoplasmosis. During murine T. gondii infection, we found mIDO1 mRNA and mIDO1 protein, as well as mIDO1-mediated tryptophan degradation in lungs of WT mice. IDO−/− mice show no tryptophan degradation in the lung during infection. Even though T. gondii is tryptophan auxotroph and rapidly replicates during acute infection, the parasite load was similar in IDO−/− mice compared to WT mice 7 days post-infection. IDO1 is described to have immunosuppressive properties, and since T cell suppression is observed during acute toxoplasmosis, we analyzed the possible involvement of mIDO1. Here, we did not find differences in the intensity of ex vivo mitogen stimulated T cell proliferation between WT and IDO−/− mice. Concomitant nitric oxide synthase inhibition and interleukin-2 supplementation increased the T cell proliferation from both genotypes drastically, but not completely. In sum, we analyzed the involvement of mIDO1 during acute murine toxoplasmosis in our specifically adjusted experimental model and found a definite mIDO1 induction. Nevertheless, mIDO1 seems to be functional redundant as an antiparasitic defense mechanism during acute toxoplasmosis in mice. Furthermore, we suggest that the systemic T cell suppression observed during acute toxoplasmosis is influenced by nitric oxide activity and IL-2 deprivation.